Epigenetic: a molecular link between testicular cancer and environmental exposures - Vega, Aurelie; Baptissart, Marine; Caira, Françoise; Brugnon, Florence; Lobaccaro, Jean-Marc A.; VOLLE, David H. (Frontiers in Endocrinology, 2012)
In the last decades, studies in rodents have highlighted links between in utero and/or neonatal exposures to molecules that alter endocrine functions and the development of genital tract abnormalities, such as cryptorchidism, hypospadias, and impaired spermatogenesis. Most of these molecules, called endocrine disrupters (EDs) exert estrogenic and/or antiandrogenic activities. These data led to the hypothesis of the Testicular Dysgenesis Syndrome which postulates that these disorders are one clinical entity and are linked by epidemiological and pathophysiological relations. Futhermore, infertility has been stated as a risk factor for testicular cancer. The incidence of testicular cancer has been increasing over the past decades. Most of testicular germ cell cancers develop through a pre-invasive carcinoma in situ (CIS) from fetal germ cells (primordial germ cell or gonocyte). During their development, fetal germ cells undergo epigenetic modifications. Interestingly, several lines of evidence have shown that gene regulation through epigenetic mechanisms (DNA and histone modifications) plays an important role in normal development as well as in various diseases, including testicular cancer. Here we will review chromatin modifications which can affect testicular physiology leading to the development of testicular cancer; and highlight potential molecular pathways involved in these alterations in the context of environmental exposures.